Effect of chlorination on the assessment of waste engine oil modified asphalt binders. (19th March 2019) - Al-Mutlaq, Shaymaà; Mahal, Ehab; Yahya, Rosiyah; Mahal, Ahmed
Abstract: The main objective of this study is to develop a new asphalt binder using waste engine oil (WEO) and improve its properties especially the resistance to rutting, reduces thermal susceptibility as well as the solubility in kerosene. The properties of WEO binders were modified further by chlorine. All blends were evaluated using Fourier transform infrared (FT–IR) spectroscopy, Thermal gravimetric analysis (TGA) differential scanning calorimetry (DSC) and dynamic shear rheometer (DSR). Asphalt binder specimens containing different concentrations (0, 2, 4, 6, and 8) % of waste engine oil with and without chlorine gas were fabricated.